Traffic risk perception and behavioral intentions of paratransit users in Phnom Penh. (May 2018) - Phun, Veng Kheang; Kato, Hironori; Yai, Tetsuo
Highlights: We explored traffic risk's effects on behavioral intentions in paratransit users. We used structural equation modeling with questionnaire survey data in Phnom Penh. The effects were significant for motorcycle taxi but not for auto-rickshaw users. Users tolerated the traffic risk and would continue using motorcycle taxis. Motorcycle taxi users tended to shift to a new public transport when available. Abstract: Paratransit in Asian developing cities operates under high risk of traffic accidents because of dangerous driving behavior and use of old, poorly maintained, overloaded, and non-standardized vehicles. We explore the effects of traffic risk perception on satisfaction and behavioral intentions of paratransit users. Behavioral intentions comprised user loyalty and intention towards a new (safer and more comfortable) public transport mode. The effects were investigated using structural equation modeling based on data collected from 484 motorcycle taxi and 272 auto-rickshaw users in Phnom Penh, Cambodia, between May 13 and 20, 2016. For motorcycle taxi users, the results showed that traffic risk perception had a direct negative effect on satisfaction and positive effects on user loyalty and perception of new public transport. Users were dissatisfied with the risk of traffic accidents involving motorcycle taxi services, but tolerated the risk and would continue using the service. They were further likely to shift to the new public transport mode when that mode became available. All effects were nonsignificant for auto-rickshaw users. Feasible policy implications of our results are discussed, along with recommendations to improve paratransit safety and users' traffic risk perception.